Proximal aortic stiffness modifies the relationship between heart rate and backward wave and hence central arterial pulse pressure - Mthembu, Nonhlanhla; Peterson, Vernice R.; Norton, Gavin R.; Sadiq, Eitzaz; Kolkenbeck-Ruh, Andrea; Naran, Ravi; Yusuf, Suraj M.; Tade, Grace; Bello, Hamza; Bamaiyi, Adamu; Libhaber, Carlos D.; Dessein, Patrick; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aims A lower heart rate (HR) increases central blood pressure through enhanced backward wave pressures (Pb). We aimed to determine whether these relationships are modified by increases in aortic stiffness. Methods Using non-invasive central pressure, aortic velocity and diameter measurements in the outflow tract (echocardiography), we assessed the impact of aortic stiffness on relationships between HR and arterial wave morphology in 603 community participants < 60 years of age, 221 ≥ 60 years, and in 287 participants with arterial events [stroke and critical limb ischemia (CLI)]. Results As compared to community participants < 60 years, those ≥ 60 years or with events had increased multivariate adjusted proximal aortic characteristic impedance (Zc) and carotid femoral pulse wave velocity (PWV) (p < 0.05 to < 0.0001). Community participants ≥ 60 years and those with events also had a greater slope of the inverse relationship between HR and Pb (p < 0.001 for comparison). While in community participants < 60 years, no interaction between indexes of aortic stiffness and HR occurred, in those ≥ 60 years (p < 0.02) and in those with arterial events (p = 0.001), beyond aortic root diameter, an interaction between Zc and HR, but not between PWV and HR independently associated with Pb. This translated into stepwise increases in the slope of HR-Pb relationships at incremental tertiles of Zc. Although HR was inversely associated with the systemic reflection coefficient in community participants ≥ 60 years (p < 0.0001), adjustments for the reflection coefficient failed to modify HR-Pb relations. Conclusion Beyond the impact on systemic wave reflection, increases in proximal aortic stiffness enhance the adverse effects of HR on Pb and hence central BP.